‘Scripture grows with its readers’: doctrinal development from a Ricœurian perspective - Aspray, B (Wiley, 2019)
This article uses the hermeneutic philosophy of Paul Ricœur to contribute to a Protestant‐ecumenical understanding of doctrinal development, construed as the growth of the meaning of Scripture. Ricœur’s hermeneutics differ from those of Gadamer, structuralism, and authorial intention in ways that, unlike these, show how doctrinal development is not only possible but necessary. With a Ricœurian approach to biblical interpretation, I argue that doctrinal and even dogmatic development is fully compatible with a Protestant commitment to sola scriptura.